RESPON PERTUMBUHAN TINGGI BIBIT GAHARU (Aquilariamalaccensis) TERHADAP KOMBINASI PERLAKUAN MEDIA, NAUNGAN DAN SUNGKUP PLASTIK - Abdi Rahim Yudani; Basir Basir; Sulaiman Bakri (Universitas Lambung Mangkurat, 2020)
Agarwood is one of the many non-timber forest product commodities that has an important role in terms of increasing the country's foreign exchange.One of the plant commodities is agarwood (Aquilaria malaccensis). The purpose of this study was to analyze the growth response of agarwood seedlings on a combinations of media treatment, shade and plastic covers. The experimental design used wasa factorial inthe completely randomized design with three factors: media, shade, and plastic cover. The variable measured was the height increment. The results showed that a combination of 75% topsoil with a mixture of 25% sand under 50% paranet shade and using a plastic cover provided a very significant effect on height. The highest increment height was 12.22 cm.Keywords: Aquilaria malaccensis, shade level, plastic hood, growth response